2023
DOI: 10.1108/ijesm-07-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between tourism development, environmental quality and economic growth. Does renewable energy help in achieving carbon neutrality goal?

Abstract: Purpose The current study aims to ascertain the association between tourism development, economic growth and environmental quality by using the short-run and long-run autoregressive distributive lag model. Design/methodology/approach Tourism development has a major role to play in improving a nation’s economic growth. However, it is also blamed for exacerbating environmental pollution because of its massive use of energy (non-renewable energy). Findings The major findings of this research show that renewab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The research further concluded that a bidirectional causal link exists between GDP and REC. SimilarlyBanga et al (2023) inspected Understanding the Dynamics of Political Economy in Relation to Energy Transition for G7 Economies also claimed that NRR can be used as an important metric among all renewable energy products and technologies, which could help generate renewable electricity in diff erent regions. In one of the prevailing perspectives,Jin and Huang (2023) evaluated that economic expansion and use of resources improve the load factor of renewable electricity and confi rmed a bidirectional linkage between the variables.…”
mentioning
confidence: 99%
“…The research further concluded that a bidirectional causal link exists between GDP and REC. SimilarlyBanga et al (2023) inspected Understanding the Dynamics of Political Economy in Relation to Energy Transition for G7 Economies also claimed that NRR can be used as an important metric among all renewable energy products and technologies, which could help generate renewable electricity in diff erent regions. In one of the prevailing perspectives,Jin and Huang (2023) evaluated that economic expansion and use of resources improve the load factor of renewable electricity and confi rmed a bidirectional linkage between the variables.…”
mentioning
confidence: 99%